Effect of surface orientation on the tribological properties of laser sintered polyamide 12. (December 2015) - Bai, Jiaming; Yuan, Shangqin; Chow, Wanlu; Chua, Chee Kai; Zhou, Kun; Wei, Jun
Abstract: Experiments have been carried out to determine the tribological properties of laser sintered polyamide 12 (PA12). The effect of surface orientation on the wear properties was studied, which showed anisotropic behaviour. Laser sintered specimens were polished to achieve better surface finish for the wear tests. Tribological testing results showed that the wear resistance was greater and the coefficient of friction was smaller for the side surfaces as compared to the top surfaces. Experimental details and possible reasons for the results obtained are further discussed in the paper.